HUBUNGAN ANTARA NILAI TUGAS DAN NILAI KEAKTIFAN DALAM KELAS TERHADAP NILAI UJIAN AKHIR SEMESTER TELAAH KURIKULUM MATEMATIKA SMA PADA MAHASISWA PENDIDIKAN MATEMATIKA IKIP PGRI BALI TAHUN PELAJARAN 2015/2016 - I Komang Sukendra (FPMIPA IKIP PGRI Bali, 2016)
The Relationship Between The Value of Assignment and The Activity in The Class to Students Final Semester Examination Value in The Analysis of Mathematics Lecterature at IKIP PGRI Bali in 2015/2016 Curriculum is a set of planning and knowledge concerning to content and lesson, the methode as well functioning as guidance of studying-teaching activity performance. Curriculum is the tool functioning to achevive aducation goal. The student as teacher candidates are obligated to comprehend curriculum applied in present time. In the process of studying, some problems caused by some factors either from internal or external of the students themselves are often found. The aim expected in this study or paper is to know the relationship between assignment value and student activities in the class to final semester examination value. This study aimed to know how far the influence I between free variabel and bound variabel to mathematic curriculum. Examined to the fourth semester mathematics students of IKIP PGRI Bali by taking purposive sampling. The data analysis were used by using double linear registrasi similarity. Based on analysis data, it was found that the value of student assignment and the activity in the class simultaneously influenced to final semester examination value of SMA curriculum mathematics approach lecture. And the activity in the class had higher influence than the student assignment value. Based on the such result, before the student. When to the field to teach, the student were obligated to make assignment and activity in the class hopely, the could make planing of the study based on the syllabus matched whit the effective curriculum in the practice of teaching in the field.